THE SIGNIFICANT ROLE OF FINTECH IN EMPOWERING STUDENTS IN THE DIGITAL ERA: AN ANALYSIS WITHIN THE CONTEXT OF DIGITAL FINANCIAL TRANSFORMATION - Soviatri, Mita; Rismawati (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2024)
The aim of this study is to delve into the extent to which students at Muhammadiyah University Palopo comprehend and exhibit interest in fintech, and to investigate the role of Financial Technology (Fintech) in empowering students in the digital era through digital financial transformation. This research adopts a quantitative approach, utilizing primary data, with the study population targeted towards users of Financial Technology (Fintech) services, specifically students enrolled in the Faculty of Economics and Business, Management Program, at Muhammadiyah University Palopo, encompassing approximately 133 individuals, determined using the Slovin formula. This research analysis was conducted using multiple linear regression with the data processing tool, SPSS version 26 (Statistical Product and Service Solutions). The results indicate that Fintech has a positive and significant influence on student empowerment. However, Digital Financial Transformation in this study did not exert a significant influence on student empowerment. This suggests that, within the context of this research, Digital Financial Transformation does not have a noteworthy impact on enhancing student empowerment.